Hubungan antara Pengetahuan Wanita Hamil pada Trimester Pertama dan Penggunaan Aromaterapi Minyak Peppermint untuk Meredakan Mual dan Muntah di Klinik Pelayanan Kesehatan Primer Ar-Razi pada Tahun 2025 - Hasibuan, Namiroh Falah; Sinaga, Hariana Erdewi (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
The type of research used in this study is quantitative descriptive. Quantitative descriptive research involves describing, investigating, and explaining something as it is, and drawing conclusions from observable phenomena using numerical data. The researcher aims to determine the relationship between the use of peppermint essential oil aromatherapy and nausea and vomiting in pregnant women in the first trimester at Ar-Razi Primary Clinic in 2025. It was found that out of 30 respondents, 6 women (20.0%) had good knowledge, 6 women (20.0%) had a fast process of nausea and vomiting relief, and 0 women (0%) had a slow process. Among first-trimester pregnant women, 5 women (16.0%) had adequate knowledge, and 1 (4.0%) did not experience rapid relief. Among pregnant women in the first trimester, 1 (3.3%) had insufficient knowledge, and 17 (56.7%) did not experience rapid relief from nausea and vomiting. There is a relationship between the knowledge of pregnant women in the first trimester about the benefits of peppermint oil aromatherapy and the efficiency of nausea and vomiting at the Ar-Razi Primary Clinic in 2025, as indicated by the sig. value of 0.00 < α value of 0.05. This study found a relationship between the use of peppermint oil aromatherapy and nausea and vomiting in first-trimester pregnant women at the Ar-Razi Clinic in 2025. It is recommended that first-trimester pregnant women understand the use of peppermint oil aromatherapy for reducing nausea and vomiting.